Silver decorated 2D nanosheets of GO and MoS2 serve as nanocatalyst for water treatment and antimicrobial applications as ascertained with molecular docking evaluation. (1st April 2021) - Qumar, U; Hassan, J; Naz, S; Haider, A; Raza, A; Ul-Hamid, A; Haider, J; Shahzadi, I; Ahmad, I; Ikram, M
Abstract: In this work, synthesis of graphene oxide (GO) and reduced graphene oxide (rGO) was realized through a modified Hummers route. Different concentrations (5 and 10 wt%) of Ag were doped in MoS2 and rGO using a hydrothermal technique. Synthesized Ag-MoS2 and Ag-rGO were evaluated through XRD that confirmed the hexagonal structure of MoS2 along with the transformation of GO to Ag-rGO as indicated by a shift in XRD peaks while Mo–O bonding and S=O functional groups were confirmed with FTIR. Morphological information of GO and formation of MoS2 nanopetals as well as interlayer spacing were verified through FESEM and HRTEM respectively. Raman analysis was employed to probe any evidence regarding defect densities of GO. Optical properties of GO, MoS2, Ag-rGO, and Ag-MoS2 were visualized through UV–vis and PL spectroscopy. Prepared products were employed as nanocatalysts to purify industrial wastewater. Experimental results revealed that Ag-rGO and Ag-MoS2 showed 99% and 80% response in photocatalytic activity. Besides, the nanocatalyst (Ag-MoS2 and Ag-rGO) exhibited 6.05 mm inhibition zones against S. aureus gram positive (G+) and 3.05 mm for E. coli gram negative (G-) in antibacterial activity. To rationalize biocidal mechanism of Ag-doped MoS2 NPs and Ag-rGO, in silico molecular docking study was employed for two enzymes i.e. β -lactamase and D-alanine-D-alanine ligase B (ddlB) from cell wall biosynthetic pathway and enoyl-[acylcarrier-protein] reductase (FabI) from fatty acid biosynthetic pathway belonging to S. aureus . The present study provides evidence for the development of cost-effective, environment friendly and viable candidate for photocatalytic and antimicrobial applications.